Design and Development of F1 in Schools Racetrack System: Gate Timing System - Muhammad Hafiz Mohd Fauzi,; Nurzaki Ikhsan,; Ramlan Kasiran,; Mohd Hanif Mat, (International Journal of Integrated Engineering, 2024)
This study addressed the problem of improving the gate timing system for F1 in School Competition. The current available gate timing system was not flexible in terms of obtaining result data and was costly. To overcome this challenge, a novel cost-effective timing system was proposed. This system incorporated design enhancements, particularly the introduction of flexible sector gates. These modifications offered users valuable insights into their vehicles' performance. The objective was to propose an innovative design for the F1 in School gate timing system, emphasizing the significance of accurate, cost-effective technology in fostering growth and success in student competitions. This was accomplished by developing two essential components, involving the software and hardware. The software production consisted of components such as Arduino Mega, NodeMCU ESP8266, and Nextion LCD display, while the hardware components were assembled from ultrasonic sensors, LEDs, buttons, and many more. The development of the prototype resulted in a well-functioning gate timing system with the capacity to record results wirelessly through a website and the flexibility required for configuring sector gates. In addition to enhancing user comprehension of their vehicle's performance, the adaptability of the sector gates allowed for more accurate results that could be converted into a plot. This research encouraged the user, mainly a secondary student, to appreciate the impact of science, technology, engineering, arts, and mathematics (STEAM) related fields and the potential for global commercialization value.